IMPLEMENTASI KEBIJAKAN PERATURAN PEMERINTAH NO 38/2012 TENTANG PENGEMBANGAN KINERJA PNS MELALUI PELATIHAN DAN PENGEMBANGAN (STUDI DI LEMBAGA KEPRESIDENAN TIMOR-LESTE) - Anacleto Pinto; Saleh Soeaidy; Andy Fefta Wijaya (REFORMASI, 2015)
This study contains the efforts of the Government of Timor-Leste in enhancing the development and performance of Civil Servants capacity through education and training, both domestically and abroad. Implementation of the policy / regulation is considered very important because it is through education and training is expected to increase the knowledge, abilities, and skills in improving the performance of civil servants. With adannya education and training program, each employee is expected to be able to work well in providing services to the public. This study menggunKn descriptive qualitative method. Research results show that the Implementation / Government Regulation No. 38/2012 on performance development through education and training of civil servants at the Presidential Institution of Timor-Leste has been running with no maximum. As for some of the factors that become an obstacle to the implementation of the policy / rule is that some political elements, the low educational level of employees, lack of employees in implementing the program.